Strategies to Prevent and Reform Violence by Police Officers through a Criminological Approach in the South Sulawesi Regional Police - Marikar Marikar; Hambali Thalib; Abd Rahman; Ilham Abbas (Fakultas Hukum, Universitas Muslim Indonesia, 2025)
This study examines criminological strategies to prevent and reform police violence within the South Sulawesi Regional Police. Using qualitative empirical data from interviews and official records, the study finds that police violence occurs in physical, armed, and verbal forms, driven by individual stress, situational pressures, organizational culture, and weak institutional control. The findings demonstrate that disciplinary or repressive measures alone are insufficient to ensure lasting behavioral change. Effective prevention and reform require an integrated, layered approach combining primary prevention (ethical and human rights training, selective recruitment), secondary prevention (early detection, psychological assessment, mentoring, and supervision), and tertiary prevention (rehabilitation and behavioral reorientation), reinforced by accountable legal mechanisms, community participation, and psychological interventions. Integrating penal and non-penal approaches within a criminological framework provides a more sustainable model for fostering professional, humanistic policing and restoring public trust in a democratic rule-of-law state